Recreation attachment toward Tehran botanical garden: a Q-method inquiry - Jamaludin, Mazlina; Aziz, Azlizam; Sarookhani, Farzaneh; Mariapan, Manohar (Global Academic Excellent, 2018)
The Tehran National Botanical Garden has provided a considerable range of recreation benefits for urban communities over the past 100 years. Local communities are attached to the garden as a recreation place mainly due to environmental benefits and psychological attachment. The theory of place attachment and Q-method have been used to investigate visitors' perception, feeling, and attachment to this place. The three factors emerging from the Q-sort data were identified as educational factor, emotional factor, and functional factor. These factors represented visitors' point of view about the "place meaning" of the Tehran National Botanical Garden. The results can aid decision makers in reformulating the planning and management process to improve the recreation place role of the botanical gardens in the city for the benefit of the communities.